Aluminum alloy surface laser alloying layer and preparation method and application thereof
Through the surface of the aluminum alloy collision beam surface, nickel -titanium alloy and graphite nitride powder are used for laser alloying to form a fine crystal reinforcement coating, which solves the intensity and toughness of the existing aluminum alloy collision beam. The problem realizes higher abrasion resistance, strong toughness and service life, while reducing manufacturing costs.
Patent Information
- Application Number
- CN202411503252.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
During the mass production process of existing aluminum alloy anti-collision beams, there are problems such as excessive weight, easy rust, poor shock absorption effect and high manufacturing costs, making it difficult to effectively improve their strength and toughness.
The aluminum alloy is used as the base material, and the laser alloy layer is prepared by coating the nickel -titanium alloy powder and graphite nitride powder on its surface, and the laser alloy layer is prepared through laser alloy technology to form a fine crystal reinforced coating.
It significantly improves the abrasion resistance, strong toughness and service life of aluminum alloy collision beams. At the same time, it maintains lightweight characteristics, reduces manufacturing costs, and is suitable for mass production.
Smart Images

Figure CN119372638A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal surface treatment, in particular to the technical field of automobile anti-collision beam surface treatment, and specifically to a laser alloying layer on the surface of an aluminum alloy and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the continuous increase in the number of cars, automobile products have gradually become a part of people's lives. The rapid increase in the number of cars has made environmental protection and safety issues increasingly prominent, and the lightweight design of automobiles has also received more and more attention. With the development of automobile lightweight technology, more and more automobile parts have been put on the agenda for weight reduction. Not only modified plastic materials are used in interior decoration, doors, front panels, seats and other parts, but also modified plastics are used in automobile fuel tanks, tailgates and bumpers. For automobile anti-collision beams, while ensuring safety performance and reducing its weight, it is necessary to improve structural performance and effectively absorb impact energy to reduce damage to the passenger compartment and body structure. This poses a challenging issue for industry insiders in the structural design of anti-collision beams.
[0004] Aluminum alloys can have high strength while maintaining the advantages of pure aluminum such as light weight and good corrosion resistance. At present, a variety of aluminum alloys are used to prepare automobile anti-collision beams. For example, 6000 series aluminum alloy extrusion products are widely used as automobile energy-absorbing components (such as automobile anti-collision beams) due to their low density, high specific strength and specific stiffness, good elasticity and impact resistance. 7000 series (A1-Zn-Mg series) aluminum alloys are also called super-hard aluminum. They belong to high-strength aluminum alloys and are widely used in safety structural parts such as automobile bumpers and door anti-collision beams. However, the strength of most lightweight materials is not high. In the process of large-scale mass production, aluminum alloys have negative problems such as excessive weight, easy rust, poor shock absorption effect, and higher manufacturing costs. These problems are difficult to be cured, and the negative effects are far greater than the positive benefits. Therefore, it is urgent to develop high-strength, high-toughness, collision-resistant aluminum alloy materials to improve the service life of aluminum alloy anti-collision beams under complex working conditions. Summary of the invention
[0005] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide an aluminum alloy surface laser alloying layer and a preparation method and application thereof. The aluminum alloy surface laser alloying layer provided by the present invention can improve the strength and toughness of the aluminum alloy without affecting its lightweight, and can be used to prepare alloyed aluminum alloy anti-collision beams for automobiles. The prepared anti-collision beams have excellent wear resistance, strength and toughness, and longer service life, and the process is simple, the cost is low, and the material is saved, so it is suitable for mass production and has significant economic benefits.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] The first aspect of the present invention provides an aluminum alloy surface laser alloying layer, which uses aluminum alloy as a base material, and nickel-titanium alloy powder and graphite phase carbon nitride (g-C3N4) powder as a coating material coated on the base, and is obtained by laser alloying. In the coating material, the amount of graphite phase carbon nitride powder is 1.5 to 2.5% of the nickel-titanium alloy powder.
[0008] In some embodiments of the present invention, the particle size of the nickel-titanium alloy powder is 60 to 125 μm;
[0009] The particle size of the graphite phase carbon nitride powder is 1 to 10 μm.
[0010] In some embodiments of the present invention, the thickness of the laser alloying layer on the surface of the aluminum alloy is 0.25-1.0 mm.
[0011] A second aspect of the present invention provides a method for preparing the above-mentioned aluminum alloy surface laser alloying layer, comprising the following steps:
[0012] Milling, cleaning and drying the base material for later use;
[0013] The nickel-titanium alloy powder and the graphite phase carbon nitride powder are mixed and ball-milled to obtain a ground composite powder;
[0014] The composite powder is placed on the surface of a substrate, and then the surface of the substrate is subjected to laser alloying treatment to obtain a laser alloyed layer on the surface of an aluminum alloy.
[0015] In some embodiments of the present invention, the specific method of milling, cleaning and drying is: milling the working surface of the base material by 0.15-0.25 mm, cleaning it with anhydrous ethanol, and then drying the base surface.
[0016] In some embodiments of the present invention, the ball-to-material volume ratio in the ball milling is 2.5-3.5:1, and the ball milling time is 6-12 hours.
[0017] In some embodiments of the present invention, the composite powder is transported to the surface of the processed matrix material to be alloyed by coaxial powder feeding.
[0018] In some embodiments of the present invention, the process parameters of the laser alloying are: laser power of 3.5-4.0KW, rectangular spot of 2×14mm, overlap rate of 10-30%, scanning speed of 550-700mm / min, protective gas of argon, powder feeding speed of 1.5-4.5g / s, and powder feeding gas flow rate of 7.5-8.5L / min.
[0019] In some embodiments of the present invention, after the laser alloying treatment is completed, the obtained laser alloyed layer is ground and polished with a grinding amount of 0.1 to 0.2 mm; the surface condition of the laser alloyed layer after grinding and polishing is checked; the surface of the laser alloyed layer with defects is locally ground and partially re-laser alloyed.
[0020] The third aspect of the present invention provides an application of the above-mentioned aluminum alloy surface laser alloying layer or the aluminum alloy surface laser alloying layer obtained by the above-mentioned preparation method in enhancing the wear resistance, toughness and collision energy absorption characteristics of the aluminum alloy substrate.
[0021] In some embodiments of the present invention, the aluminum alloy matrix material is an automobile aluminum alloy anti-collision beam.
[0022] The beneficial effects of the present invention are:
[0023] The present invention provides a laser alloying layer on the surface of an aluminum alloy. By adding g-C3N4 powder to nickel-titanium alloy metal powder, during the rapid cooling process of laser alloying, the refractory metal or ceramic phase serves as the core of heterogeneous nucleation, so that the prepared coating is fine-grained and strengthened, thereby improving the strength and toughness of the coating, and not generating crack problems while maintaining the high hardness of the coating. The laser alloying layer on the surface of the aluminum alloy prepared by the present invention has obvious grain refinement, achieving the purpose of fine-grain strengthening, ensuring that the coating has high hardness and high toughness, thereby greatly improving the collision resistance of the aluminum alloy, and further improving the service life of the aluminum alloy anti-collision beam under complex working conditions.
[0024] The present invention optimizes the design object of lightweight strength of aluminum alloy anti-collision beams, and uses laser alloying technology to prepare laser alloying strengthening coatings on the surface of aluminum alloy anti-collision beams. The extremely fast heating and cooling speed of laser alloying technology can make the extremely thin surface high-performance alloying powder react quickly with the surface of the aluminum alloy anti-collision beam substrate, so that the laser alloying layer of the prepared aluminum alloy anti-collision beam has a fine structure, which significantly improves the wear resistance and toughness of the aluminum alloy anti-collision beam and extends its service life. Laser alloying powder uses nickel-titanium alloy and carbon nitride composite powder. By using the synergistic effect of the two, it can meet the use requirements of the wear resistance and toughness of the alloy anti-collision beam, and the service life can reach more than twice that of the new aluminum alloy anti-collision beam without laser alloying, realizing the combination of dispersion strengthening and hard phase strengthening. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 The present invention is a flow chart of the process for preparing a laser alloying layer on the surface of an aluminum alloy according to an embodiment of the present invention. DETAILED DESCRIPTION
[0027] A typical embodiment of the present invention provides an aluminum alloy surface laser alloying layer, which uses aluminum alloy as a base material, and nickel-titanium alloy powder and graphite phase carbon nitride powder as coating materials coated on the base, and is prepared by laser alloying. In the coating material, the amount of graphite phase carbon nitride powder is 1.5 to 2.5% of the nickel-titanium alloy powder.
[0028] In actual production, the aluminum alloy matrix of the present invention can be the aluminum alloy anti-collision beam substrate of the automobile. The purpose of the present invention is to achieve the lightweight structure of the automobile body while reducing the impact on the passengers, drivers and pedestrians in the car in the event of a collision accident, thereby protecting the safety of the personnel, while improving the performance of the vehicle and reducing casualties. In this regard, the present invention takes the lightweight strength optimization design of the aluminum alloy anti-collision beam as the object, and prepares the laser alloying strengthening coating on the surface of the aluminum alloy anti-collision beam by using laser alloying technology. The laser alloying powder adopts nickel-titanium alloy and carbon nitride composite powder. Nickel-titanium alloy is a high-quality lightweight material. Because its density is much lower than that of steel, the quality of the bumper assembly made of nickel-titanium alloy is much lower than that of the bumper made of steel while ensuring that the strength and stiffness of the aluminum alloy anti-collision beam remain unchanged. In addition, nickel-titanium alloy also has many high-quality properties, such as shape memory function, because in the event of a car expansion accident, the expansion deformation will be reduced due to the restoring force, so the collision repair cost can be reduced. Graphite carbon nitride (g-C3N4) powder is an organic semiconductor material with relatively stable, fluffy and porous characteristics. It is expected to effectively improve the stiffness, strength and collision energy absorption characteristics of the anti-collision beam assembly, ensure its rear-end collision safety performance, and at the same time achieve the purpose of reducing the total weight of the vehicle. According to the working requirements of the aluminum alloy anti-collision beam, by using a special ratio of metal component powder and graphene powder, and utilizing the synergistic effect of the two, it can meet the wear resistance and toughness requirements of the alloy anti-collision beam, and the service life can reach more than twice that of the new aluminum alloy anti-collision beam without laser alloying, realizing the combination of dispersion strengthening and hard phase strengthening.
[0029] The present invention adds g-C3N4 powder to nickel-titanium alloy metal powder. During the rapid cooling process of the alloying layer, the refractory metal or ceramic phase serves as the core of heterogeneous nucleation, so that the prepared coating is fine-grained and strengthened, thereby improving the toughness of the coating, and preventing cracks from occurring while maintaining high hardness of the coating. The laser alloying layer on the surface of the aluminum alloy prepared by the present invention has obvious grain refinement, achieving the purpose of fine-grain strengthening, ensuring that the coating has high hardness and high toughness, thereby greatly improving the collision resistance of the aluminum alloy, and further improving the service life of the aluminum alloy anti-collision beam under complex working conditions.
[0030] In some examples of this embodiment, the particle size of the nickel-titanium alloy powder is 60 to 125 μm; the particle size of the graphite phase carbon nitride powder is 1 to 10 μm.
[0031] In some examples of this implementation manner, the thickness of the laser alloying layer on the surface of the aluminum alloy is 0.25 to 1.0 mm.
[0032] A second aspect of the present invention provides a method for preparing the above-mentioned aluminum alloy surface laser alloying layer, comprising the following steps:
[0033] Milling, cleaning and drying the base material for later use;
[0034] The nickel-titanium alloy powder and the carbon nitride powder are mixed and ball-milled to obtain a ground composite powder;
[0035] The composite powder is placed on the surface of a substrate, and then the surface of the substrate is subjected to laser alloying treatment to obtain a laser alloyed layer on the surface of an aluminum alloy.
[0036] The present invention adopts laser alloying technology, and utilizes the characteristics of laser alloying technology with extremely fast heating and cooling speed, so that the extremely thin high-performance alloyed powder can react with the surface of the aluminum alloy anti-collision beam substrate quickly, so that the laser alloying layer of the aluminum alloy anti-collision beam obtained is refined, which significantly improves the wear resistance and toughness of the aluminum alloy anti-collision beam and prolongs its service life. According to the working requirements of the aluminum alloy anti-collision beam, the present invention adopts a special ratio of metal component powder and graphene powder to meet the use requirements of the wear resistance and toughness of the alloy anti-collision beam, and the service life can reach more than twice that of the new aluminum alloy anti-collision beam without laser alloying, realizing the combination of dispersion strengthening and hard phase strengthening. The present invention uses a laser alloying process to sequentially form an alloying layer, a bonding area, a heat-affected zone and a matrix on the surface of the aluminum alloy anti-collision beam, wherein the performance of the alloying layer and the organizational morphology and comprehensive organizational quality of the bonding area are better than the performance of the original substrate, thereby achieving the strengthening of the aluminum alloy anti-collision beam.
[0037] In some examples of this implementation mode, the specific method of milling, cleaning and drying is: milling the working surface of the base material by 0.15-0.25 mm, cleaning it with anhydrous ethanol, and then drying the base surface. The present invention cleans the surface of the aluminum alloy anti-collision beam to be strengthened with industrial alcohol, so that the aluminum alloy anti-collision beam can be better laser alloyed during the preparation process, thereby improving the qualified rate of the laser alloyed aluminum alloy anti-collision beam.
[0038] In some examples of this implementation mode, the ball-to-material volume ratio of the ball milling is 2.5 to 3.5:1, and the ball milling time is 6 to 12 hours. Specifically, the ball milling can be performed using a ball mill, such as placing the mixed powder into a high-energy ball mill for ball milling, wherein the grinding balls used in the ball milling are corundum balls with diameters of 1 mm and 3 mm, the number ratio of the two grinding balls is 1:4, the ball-to-material volume ratio is 3:1, and the ball milling time is 6 to 12 hours to obtain a ground composite powder for standby use.
[0039] In some examples of this embodiment, the composite powder is transported to the surface of the processed matrix material to be alloyed by coaxial powder feeding.
[0040] In some examples of this implementation mode, the process parameters of the laser alloying are: laser power is 3.5~4.0KW, rectangular spot is 2×14mm, overlap rate is 10~30%, scanning speed is 550~700mm / min, protective gas is argon, powder feeding speed is 1.5~4.5g / s, and powder feeding gas flow rate is 7.5~8.5L / min.
[0041] In some examples of this implementation mode, after the laser alloying treatment is completed, the obtained laser alloying layer is ground and polished, and the grinding amount is 0.1-0.2 mm; the surface condition of the laser alloying layer after grinding and polishing is checked; the surface of the laser alloying layer with defects is partially ground and partially re-laser alloyed. The substrate material with the surface laser alloying layer (i.e., the laser alloyed aluminum alloy anti-collision beam) that has passed the inspection can be directly packed for standby.
[0042] When the aluminum alloy matrix material is an aluminum alloy anti-collision beam, an aluminum alloy anti-collision beam with a laser alloying layer on the surface (referred to as laser alloyed aluminum alloy anti-collision beam) is prepared by the above method. The surface of the laser alloyed aluminum alloy anti-collision beam sequentially forms an alloying layer, a bonding zone, a heat-affected zone and a matrix, wherein the performance of the alloying layer and the morphology and comprehensive quality of the bonding zone are better than the performance of the original substrate; the laser alloyed aluminum alloy anti-collision beam has excellent wear resistance, toughness, better protection of human life safety after collision, energy absorption and collapse, reduced vehicle weight and center of gravity, and cost savings.
[0043] The third aspect of the present invention provides an application of the above-mentioned aluminum alloy surface laser alloying layer or the aluminum alloy surface laser alloying layer obtained by the above-mentioned preparation method in enhancing the wear resistance, toughness and collision energy absorption characteristics of the aluminum alloy substrate.
[0044] In some embodiments of the present invention, the aluminum alloy matrix material is an automobile aluminum alloy anti-collision beam.
[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0046] Example 1
[0047] A method for preparing a laser alloying layer on the surface of an aluminum alloy comprises the following steps:
[0048] (1) The working surface of the aluminum alloy anti-collision beam is milled by 0.2 mm, the surface of the aluminum alloy substrate to be alloyed is cleaned with industrial alcohol, and then the surface of the substrate is dried.
[0049] (2) Add 2 wt% of g-C3N4 powder with a particle size of 1 to 10 μm to NiTi powder with a particle size of 60 to 125 μm and mix. Put the mixed powder into a high-energy ball mill for ball milling. The grinding balls used in the ball milling are corundum balls with diameters of 1 mm and 3 mm, the number ratio of the two grinding balls is 1:4, the volume ratio of the balls to the materials is 3:1, and the ball milling time is 6 to 12 hours. The ground composite powder is obtained and set aside.
[0050] (3) The composite powder prepared in step (2) is conveyed to the surface of the substrate to be alloyed treated in step (1) by coaxial powder feeding for laser alloying. The process parameters of laser alloying are: laser power of 3.5-4.0KW, rectangular spot of 2×14mm, overlap rate of 10-30%, scanning speed of 550-700mm / min, protective gas of argon, powder feeding speed of 1.5-4.5g / s, and powder feeding gas flow rate of 8L / min. A collision-resistant metal-composite modified coating on the surface of aluminum alloy, i.e., a laser alloyed layer on the surface of aluminum alloy, is prepared. The thickness of the coating is 0.25-1.0mm.
[0051] (4) Grinding and polishing the laser alloyed layer on the surface of the aluminum alloy obtained in step (3); the grinding amount is 0.1 to 0.2 mm.
[0052] (5) Check the surface condition of the laser alloying layer after polishing in step (4), perform local polishing on the surface of the laser alloying layer with defects, and perform laser alloying again on the surface. The laser alloying step is the same as step (3).
[0053] (6) The laser alloyed aluminum alloy anti-collision beams that have passed the inspection are packed for use.
[0054] The hardness of the specimens before and after alloying was measured by a Vickers microhardness tester, and the measurement results are shown in Table 1. The principle of testing hardness by a Vickers microhardness tester is to use a diamond regular tetrahedron indenter with an angle of 136 degrees between the relative faces, press it into the surface of the test sample under the action of a specified load F, keep it for a period of time, then remove the load, and then measure the length of the diagonal line of the indentation. Through this length, the surface area of the indentation can be calculated, and then the average pressure on the surface area of the indentation can be calculated, that is, the Vickers hardness value of the metal is obtained, which is represented by the symbol HV.
[0055] Different types of aluminum alloy anti-collision beams were replaced. A laser alloying layer was prepared on the surface of the aluminum alloy using the method of Example 1, and the hardness of the anti-collision beam before and after alloying was tested. The test results are shown in Table 1.
[0056] Table 1 Vickers microhardness performance test values
[0057]
[0058] It can be seen from the hardness performance test in Table 1 that the hardness value of the anti-collision beam after alloying is significantly improved compared with before alloying.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A laser alloying layer on the surface of an aluminum alloy, characterized in that: The invention uses aluminum alloy as base material, and nickel-titanium alloy powder and graphite carbon nitride powder as coating materials coated on the base through laser alloying. In the coating material, the amount of graphite carbon nitride powder is 1.5-2.5% of the nickel-titanium alloy powder.
2. The aluminum alloy surface laser alloying layer according to claim 1, characterized in that: The particle size of the nickel-titanium alloy powder is 60 to 125 μm; The particle size of the graphite phase carbon nitride is 1 to 10 μm.
3. The aluminum alloy surface laser alloying layer according to claim 1, characterized in that: The thickness of the laser alloying layer on the surface of the aluminum alloy is 0.25-1.0 mm.
4. A method for preparing a laser alloying layer on the surface of an aluminum alloy according to any one of claims 1 to 3, characterized in that: The steps include: Milling, cleaning and drying the base material for later use; The nickel-titanium alloy powder and the graphite phase carbon nitride powder are mixed and ball-milled to obtain a ground composite powder; The composite powder is placed on the surface of a substrate, and then the surface of the substrate is subjected to laser alloying treatment to obtain a laser alloyed layer on the surface of an aluminum alloy.
5. The method for preparing a laser alloying layer on the surface of an aluminum alloy according to claim 4, characterized in that: The specific method of milling, cleaning and drying is: milling the working surface of the base material by 0.15-0.25 mm, cleaning it with anhydrous ethanol, and then drying the base surface.
6. The method for preparing a laser alloyed layer on the surface of an aluminum alloy according to claim 4, characterized in that: In the ball milling, the volume ratio of balls to materials is 2.5 to 3.5:1, and the ball milling time is 6 to 12 hours.
7. The method for preparing a laser alloying layer on the surface of an aluminum alloy according to claim 4, characterized in that: The composite powder is transported to the surface of the processed matrix material to be alloyed through coaxial powder feeding.
8. The method for preparing a laser alloying layer on the surface of an aluminum alloy according to claim 4, characterized in that: The process parameters of the laser alloying are: laser power of 3.5-4.0KW, rectangular spot of 2×14mm, overlap rate of 10-30%, scanning speed of 550-700mm / min, protective gas of argon, powder feeding speed of 1.5-4.5g / s, and powder feeding gas flow rate of 7.5-8.5L / min.
9. The method for preparing a laser alloyed layer on the surface of an aluminum alloy according to claim 4, characterized in that: After the laser alloying treatment is completed, the obtained laser alloying layer is ground and polished, and the grinding amount is 0.1 to 0.2 mm; the surface condition of the laser alloying layer after grinding and polishing is checked; The surface of the laser alloyed layer with defects is locally polished and laser alloyed again locally.
10. Application of the aluminum alloy surface laser alloying layer according to any one of claims 1 to 3 or the aluminum alloy surface laser alloying layer prepared by the preparation method according to any one of claims 4 to 9 in enhancing the wear resistance, toughness and collision energy absorption characteristics of the aluminum alloy substrate; Preferably, the aluminum alloy matrix material is an automobile aluminum alloy anti-collision beam.